Green havens and pollution havens - Steven Poelhekke; Rick van der Ploeg (Center for Economic Studies and ifo Institute (CESifo), 2012)
We test for pollution haven effects in outward foreign direct investment (FDI) for different sectors using a comprehensive and exhaustive dataset for outward FDI from the Netherlands, one of the most environmentally stringent countries and a major source of global FDI. Our evidence suggests that in the sectors natural resources extraction and refining, construction, retail, food processing, beverages and tobacco, and utilities, a less stringent environmental policy in the host country significantly attracts FDI. What is important for these pollution haven effects is not only regulation but also enforcement of environmental policy. In contrast to earlier results, it is not only footloose industries that display pollution haven effects, but also the traditional pollution-intensive industries. But for the sectors machines, electronics and automotive and transportation and communication a more stringent and better enforced environmental policy attracts more FDI as this may help their reputation for sustainable management and CSR. These sectors display green haven effects. These findings have important implications for the sector distribution of FDI in destination countries.
Keywords: F13; F18; F23; Q50; 330; pollution haven; green haven; FDI; environmental policy; regulation; enforcement; strategic effects; footloose industries; CSR; Direktinvestition; Niederländisch; Umweltauflage; Auslandsverlagerung; Umweltbelastung; Corporate Social Responsibility; Niederlande; Welt